Integrating Institutional Core Values into Translation Problem-Solving: A Case Study from a Public University in Indonesia - Nadia Gitya Yulianita; Usep Muttaqin; Kristianto Setiawan; Raden Pujo Handoyo (Tell : Teaching of English Language and Literature Journal, 2025)
This study investigates the integration of Universitas Jenderal Soedirman's self-values within the Fundamental Translation course. Known as Jati Diri Unsoed, these institutional values are part of a mandatory subject for all enrolled students. The research sought to evaluate the extent to which character education at the university level has been effectively implemented. The methodology began by asking students to engage in translation tasks and address the challenges encountered during the process, thereby revealing their character traits. This also enabled the lecturer to guide students toward appropriate and thoughtful solutions. Using purposive sampling, selected students’ translations were analyzed by comparing the source and target texts and aligning them with the four core values of Jati Diri Unsoed: intelligence, honesty, strength, and caring. The analysis identified several translation challenges and the techniques employed to resolve them, including amplification, implicitation, correction, addition, and other common translation issues. The findings demonstrate that the ways students addressed these challenges reflect the values of intelligence, honesty, and caring. The study concludes that character education can be effectively integrated into various academic subjects through the application of appropriate pedagogical approaches, methods, and techniques.